LEXICAL TRANSFORMATIONS USED IN SIMULTANEOUS INTERPRETATION (BY THE EXAMPLES OF ENGLISH AND FRENCH LANGUAGES): - - Raufov, Miraziz (PT. Antis International Publisher, 2025)
Objective: This study explores the role of lexical transformations in simultaneous interpretation (SI) between English and French, focusing on speeches delivered by António Guterres and Emmanuel Macron at the United Nations General Assembly. It examines how interpreters adapt linguistic and cultural nuances to ensure accurate and effective communication. Methods: The research employs a qualitative approach, analyzing real-world examples of lexical transformations, including substitution, generalization, specification, and modulation. Results: The findings highlight the importance of lexical transformations in overcoming linguistic and cultural barriers, ensuring clarity, and maintaining the speaker's intent. Novelty: This study provides a detailed analysis of lexical transformations in high-stakes diplomatic contexts, offering insights into the cognitive and linguistic strategies employed by interpreters.